A case report of hybrid surgical resection of a giant dumbbell neurinoma in the thoracic spine - I. V. Basankin; N. V. Naryzhnyi; A. A. Giulzatyan; S. B. Malakhov (Инновационная медицина Кубани, 2020)
We report the clinical case of treating a female patient with a giant dumbbell neurinoma arising from the Th1 nerve root. For the treatment of neoplasm, a hybrid surgical tactic was chosen, including Th1 hemilaminectomy, mobilization of the dorsal part of the tumor and video-assisted thoracoscopy in order to remove its intrathoracic mass. The patient developed no neurological complications after surgery. A gross total tumor resection was documented by control computed tomography. Thus, well-coordinated work of the multidisciplinary surgical team provided good oncological and functional results in the treatment of a giant neurinoma with extension into the thoracic cavity.